ANALISIS FAKTOR SOSIAL BUDAYA DAN PSIKOLOGIS YANG MEMPENGARUHI KEPUTUSAN NASABAH MEMILIH PEMBIAYAAN PADA WARUNG MIKRO (Studi pada PT Bank Syariah Mandiri Cabang Banjarmasin) - Syafril; Nuril Huda (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This study aims to find out and to analyze: (1) the influence of socio-cultural and sychological factors that influence customer decisions in choosing micro inancing in PT Bank Syariah Mandiri, Banjarmasin Branch, and (2) which Socio-cultural and psychological factors influence the clients’ decisions in choosing microfinance in PT Bank Syariah Mandiri and which factors are more dominant. The background of this research is to examine some of the results of previous researchers who claim that religious factors greatly influence the decisions in selecting the products of Islamic banks, while other researchers claim that economic factors are more dominant in deciding the selection of the products of Islamic banks. The results of this study indicate that religious, economic, reference groups, family, social class, motivation, learning and memory factors have significant influence in the decision making of microfinance BSM election, while cultural factors and perceptions do not affect the decision makings. The dominant factor in the selection of decision making of microfinance BSM is a religious factor. The results of this study are expected to be useful for Islamic banks in setting promotional strategies to improve the customer’s decision in choosing the financing of Islamic banks.